2019
DOI: 10.1088/1742-6596/1246/1/012058
|View full text |Cite
|
Sign up to set email alerts
|

A radiologic feature of spine related to musculoskeletal disorder on pedicab drivers

Abstract: Musculoskeletal disorders (MSDs) is a health problem that was results from a work and reported form repetitious movement and awkward postures. The aim of this study is identifying MSDs on pedicab drivers and analyse the radiologic features of the spine (vertebral column) related to MSDs. The research was an observational study with 30 pedicab drivers in Palembang. Musculoskeletal disorders were identified from a Nordic questionnaire whereas other factors were measured using a self-data questionnaire, and anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
4
0
3
Order By: Relevance
“…Pekerjaan dibagi menjadi ibu rumah tangga, pekerja berat (petani dan buruh), swasta (pedagang, pelayan, penjahit, dan pegawai bank), PNS, dan kelompok lainnya seperti mahasiswa dan TNI/Polri. Indeks massa tubuh dikelompokkan menjadi underweight (<18,5), normal (18,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)9), overweight (23)(24)(25)(26)(27)(28)(29)9), dan obesitas (>30) Pasien plantar fasciitis dan bukan plantar fasciitis lebih banyak seorang pekerja swasta yaitu sekitar 13 orang (25,5%) dan 12 orang (29,3%), sedangkan indeks massa tubuh terbanyak pada kategori overweight yaitu 30 orang (58,8%) dan 24 orang (58,5%) untuk pasien plantar fasciitis dan bukan plantar fasciitis.…”
Section: Metodeunclassified
See 1 more Smart Citation
“…Pekerjaan dibagi menjadi ibu rumah tangga, pekerja berat (petani dan buruh), swasta (pedagang, pelayan, penjahit, dan pegawai bank), PNS, dan kelompok lainnya seperti mahasiswa dan TNI/Polri. Indeks massa tubuh dikelompokkan menjadi underweight (<18,5), normal (18,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)9), overweight (23)(24)(25)(26)(27)(28)(29)9), dan obesitas (>30) Pasien plantar fasciitis dan bukan plantar fasciitis lebih banyak seorang pekerja swasta yaitu sekitar 13 orang (25,5%) dan 12 orang (29,3%), sedangkan indeks massa tubuh terbanyak pada kategori overweight yaitu 30 orang (58,8%) dan 24 orang (58,5%) untuk pasien plantar fasciitis dan bukan plantar fasciitis.…”
Section: Metodeunclassified
“…Aktivitas pekerjaan yang berulang-ulang dapat menyebabkan gangguan pada sistem muskuloskeletal. Kondisi ini akan menimbulkan perubahan pada gambaran radiologis 23 . Perubahan yang terjadi juga mengenai bagian plantar pedis yaitu gambaran penebalan plantar fascia dan gambaran spur pada tumit.…”
Section: Hubungan Antara Spur Calcaneus Dan Plantar Fasciitisunclassified
“…, sports and knowledge. [1][2][3][4] A survey conducted by the American Osteopathic Association (AOA) in 2013 showed that in the last 30 days about 62% of respondents complained of pain in the lower back, 53% in the neck, 38% in the shoulders, 33% in the wrists, and 31% in the back. the top.…”
Section: Introductionmentioning
confidence: 99%
“…Pain can also spread to other areas such as the upper back and groin. 5 The results of a study conducted by the Indonesian Association of Neurologists (PERDOSSI) in patients at the Cipto Mangunkusumo Hospital (RSCM) Neurology Polyclinic in 2002 found that the prevalence of NPB sufferers was 15.6%, the second highest after cephalgia.…”
Section: Introductionmentioning
confidence: 99%
“…Based on research conducted by the Community Oriented Program for Control of Rheumatic Disease (COPCORD) in 2004, the incidence of NPB in Indonesia shows 18.2% in men and 13.6% in women. 5 Low back pain is rarely fatal, but it can lead to a decrease in the functional ability of an individual with a decrease in lumbar flexibility that hinders the activities of daily living. This will directly cause a decrease in the quality of life of the individual.…”
Section: Introductionmentioning
confidence: 99%